DNA BARCODING: A USEFUL TOOL FOR FOOD INSPECTION - Cristian Bernardi; Fabio Colombo; C. Balzaretti; C. Gagliardi; P. Cattaneo (Italian Journal of Food Safety, 2011)
The central concept in species identification by molecular methods is to match the DNA sequence of unknown sample to a reference sequence through DNA sequence similarity searches. The limitation of this process is the lack of authenticated reference sequence databases. For instance, in the GenBank, the biggest database available, the sequences are accepted without any standard protocols or quality control, raising doubts over their suitability for food inspection application. Barcoding may be a tool for species identification because its aim is the production of COI (Cytochrome Oxidase subunit I) reference sequences using standard protocols. Every specimen record will not gain formal barcode status until seven data elements are placed in: species name, voucher data, collector record, identifier of specimen, COI sequence of at least 500 bp, polymerase chain reaction primers used to generate the amplicon and trace files. BOLD (Barcode of Life Data System) employs several tools to identify data anomalies or low quality records. Recently this system has been adopted in Italy too to verify the compliance of prepared fishery products with species declared in label. The authors introduce a discussion about a possible simplification of the Italian official list of seafood. especially for species of the same commercial value.